1981
DOI: 10.1111/j.1348-0421.1981.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Mycoplasma and Acholeplasma from Apparently Healthy and Diseased (Infectious Sinusitis) Turkeys

Abstract: Investigation of 136 turkeys (24 manifesting infra-orbital sinusitis, 112 apparently healthy) resulted in isolation of 79 strains of Mycoplasma and 4 of Acholeplasma. By the disc growth inhibition test with 16 reference antisera of avian serogroups, 55 strains were identified serologically and 28 remained unidentified.Thirteen strains of Mycoplasma gallisepticum, I of M. meleagridis, and 2 of Acholeplasma laidlawii were isolated from turkey sinusitis whereas serogroups C (2), D (19), F (8), M. meleagridis (4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…Similarly, higher incidence (20%) of M. gallinarum has been reported in chicken flocks of Egypt (Eissa et al, 2009). The current study revealed 1% prevalence of A. laidlawii which is in agreement with the findings of the previous study (Sayed et al, 1981) in India (Haryana) which reported the low prevalence of A. laidlawii (2.94%) by culture from turkeys affected with sinusitis. However higher incidence of A. laidlawii (20%) in healthy chicken flocks of Egypt was also reported which indicates non pathogenic nature of the organism (Eissa et al, 2009).…”
Section: Resultssupporting
confidence: 92%
“…Similarly, higher incidence (20%) of M. gallinarum has been reported in chicken flocks of Egypt (Eissa et al, 2009). The current study revealed 1% prevalence of A. laidlawii which is in agreement with the findings of the previous study (Sayed et al, 1981) in India (Haryana) which reported the low prevalence of A. laidlawii (2.94%) by culture from turkeys affected with sinusitis. However higher incidence of A. laidlawii (20%) in healthy chicken flocks of Egypt was also reported which indicates non pathogenic nature of the organism (Eissa et al, 2009).…”
Section: Resultssupporting
confidence: 92%
“…54, No. 6 (2023) DISOUKY M. MOURAD MM is mainly recovered from turkeys and characterized by poor embryonic growth performance, skeletal abnormalities, and early mortality with infrequent infraorbital sinusitis [6,7].…”
Section: Introductionmentioning
confidence: 99%